Entrepreneurs’ perceptions on the importance of proper accounting system to business / Wan Mohd Nazif Wan Mohd Nori - Wan Mohd Nori, Wan Mohd Nazif (2000)
Many research had found out that some small business entrepreneurs do not think accounting as important to their businesses and thus, no proper accounting system was adopted. Unfortunately, this has contributed, to a large extend, towards a business failure. The significant of this scenario cannot be ignored because small business entrepreneurs are the backbone of most advanced and developed nations’ national economy, including Malaysia. Despite of a tremendous effort by the government to help entrepreneurs financially as well as non-financially, there has been little research on entrepreneurs-accounting related matters.